2019
DOI: 10.1037/cns0000167
|View full text |Cite
|
Sign up to set email alerts
|

Insight from the consideration of REM dreams, non-REM dreams, and daydreams.

Abstract: Throughout history, there have been reports and claims that consideration of dreams can produce personal realizations and insight. We assessed Exploration-Insight scores associated with discussing REM and non-REM dreams in connection with recent waking life experiences. Thirty-one participants were cued in the sleep laboratory for a daydream report and then awakened from REM and N2 sleep for dream reports. Participants subsequently discussed each of their dream and daydream reports for 30 -40 min with two expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 106 publications
0
19
0
Order By: Relevance
“…We propose that the sharing of dreams has an empathic effect on the dreamer and on significant others who hear and engage with the telling of the dream. This suggested post-sleep effect of dreams can be contrasted with theories of within-sleep functions, such as that dreams reflect memory processing during sleep (Walker and Van der Helm, 2009; Blagrove et al, 2011a, b; Wamsley and Stickgold, 2011, 2018; Wamsley, 2014; van Rijn et al, 2015; Eichenlaub et al, 2018; Scarpelli et al, 2019), or reflect pre-sleep emotional waking life (Schredl, 2006; Malinowski and Horton, 2014; Blagrove et al, 2019).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…We propose that the sharing of dreams has an empathic effect on the dreamer and on significant others who hear and engage with the telling of the dream. This suggested post-sleep effect of dreams can be contrasted with theories of within-sleep functions, such as that dreams reflect memory processing during sleep (Walker and Van der Helm, 2009; Blagrove et al, 2011a, b; Wamsley and Stickgold, 2011, 2018; Wamsley, 2014; van Rijn et al, 2015; Eichenlaub et al, 2018; Scarpelli et al, 2019), or reflect pre-sleep emotional waking life (Schredl, 2006; Malinowski and Horton, 2014; Blagrove et al, 2019).…”
Section: Introductionmentioning
confidence: 90%
“…Edwards et al (2015) showed that exploration-insight scores are greater for considering dreams than for considering a recent personally significant event, where both sets of reports were discussed and explored using the Ullman procedure. Furthermore, in Blagrove et al (2019), participants rated discussions of dreams significantly higher than discussions of daydreams on exploration-insight, and also rated the statement “I learned more about issues in my waking life” more highly from discussing a dream than from discussing a daydream. These latter results were obtained even though participants did not select the dreams, as these were collected in the sleep laboratory, whereas home dreams can often be selected for sharing on the basis of appearing to be interesting, intriguing, useful or impactful.…”
Section: Introductionmentioning
confidence: 95%
“…The correspondence task was completed after these discussions. The aim of these discussions was to assess insight and personal realizations through the consideration of the reports (see Blagrove et al, 2016 Though there is considerable evidence for the dream-lag effect (Blagrove et al, 2011a;Blagrove et al, 2011b;Blagrove et al, 2014;Nielsen & Powell, 1989;Nielsen et al, 2004;Powell et al, 1995;van Rijn et al, 2015), there are also studies that find limited evidence (Nielsen & Powell, 1992) or that do not find the effect at all (Henley-Einion & Blagrove, 2014;Schredl, 2006). Despite methodological and sample size differences between previous research into the dream-lag and the present study, it is important to consider the possibility that the current non-replication shows that the dream-lag effect does not exist, and instead that waking life events gradually disappear from dreams across consecutive nights (Botman & Crovitz, 1989;Schredl, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Two to six days after the dream report collection, participants returned to the laboratory so as to clarify and discuss the content of their daydream and N2 and REM dream reports. Data for this are presented elsewhere (Blagrove et al, 2016), note that for participants with two REM dreams only one of these was clarified and discussed. After the discussions they were given the transcripts of the daydream and dream reports, and their diary records completed in the 10 days before sleeping in the sleep laboratory, so as to identify correspondences between the two sets of records, as detailed in the next section.…”
Section: Instrumental Awakenings and (Day)dream Report Collectionsmentioning
confidence: 99%
“…Blagrove (2011) proposed that whether dreams and waking life are continuous needs to be augmented by an insight dimension. It was proved that personal insight would increase by examining dream content (Edwards et al, 2015;Blagrove et al, 2019). In fact, there is also a continuity of insight function between wake and dream state.…”
Section: Introductionmentioning
confidence: 99%